2012
DOI: 10.1021/ja211515b
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Photoresponse in Organic Field-Effect Transistors

Abstract: We report on the fabrication of solution-processed organic phototransistors (OPTs) based on perylenebis(dicarboximide)s (PDIs). We found that the responsivity to the photoillumination depends on the transistor's channel length and that it can be tuned by varying the device geometry. The analysis of different morphologies of the active semiconducting layer revealed that single PDI fibers exhibit the higher photoresponse when compared to more poorly organized films. The highest responsivity value of 4.08 ± 1.65 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
98
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(103 citation statements)
references
References 36 publications
4
98
1
Order By: Relevance
“…Compared with the previously reported results, our ultrathin flat device shows the photosensitivity as high as 2.8 × 10 4 under illumination of only 100 μW cm −2 . This value is higher than most of reported results, and is in a class with the highest photosensitivity for perylene diimide derivatives as shown in Table 1 23,34,36,37,4044 . Furthermore, the previously reported n -type OPTs were fabricated on the rigid SiO 2 /Si, glass, or flexible PET, and all measurements were carried on the flat state.…”
Section: Resultscontrasting
confidence: 65%
See 1 more Smart Citation
“…Compared with the previously reported results, our ultrathin flat device shows the photosensitivity as high as 2.8 × 10 4 under illumination of only 100 μW cm −2 . This value is higher than most of reported results, and is in a class with the highest photosensitivity for perylene diimide derivatives as shown in Table 1 23,34,36,37,4044 . Furthermore, the previously reported n -type OPTs were fabricated on the rigid SiO 2 /Si, glass, or flexible PET, and all measurements were carried on the flat state.…”
Section: Resultscontrasting
confidence: 65%
“…From Fig. 3c, we calculated two important parameters of OPTs, namely, photosensitivity ( P ) and photoresponsivity ( R ), based on the following fundamental equations:where I ph is photo-current, I light is drain current under illumination, I dark is drain current under dark, A is effective device area, and P inc is incident illumination power density 34 . P and R values as function of gate voltage ( V G ) are plotted in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…OPTs are an attractive category of OFETs, which can be used as photodetectors, light‐induced switches, light‐triggered amplifiers, and image sensors, amongst other applications 15, 16, 17, 18, 19, 20, 21, 22, 23. In most studies on OPTs, it was the organic semiconductor itself, which exhibited photosensitivity.…”
mentioning
confidence: 99%
“…On the other hand, taking advantage of these features enables the realization of photosensitive transistors that can be used, e.g., for light detection and light induced switches. [6][7][8][9][10][11][12] Among the different approaches to fabricate organic thinfilm transistors, the use of self-assembled monolayers as part of a thin hybrid dielectric has proven to be a promising route to realize flexible, low-power consuming organic thin-film transistors and circuits with a promising stability. 13,14 Moreover, it has been shown that applying molecules with electron acceptor functionality in a self-assembled monolayer (SAM) on a thick SiO 2 dielectric leads to a large photosensitivity in combination with pentacene as the semiconductor.…”
mentioning
confidence: 99%